Synthesis and physical-chemical properties of 8-benzylidenhydrazino-1-(4-fluorobenzyl)theobromine derivatives - D. G. Ivanchenko; M. I. Romanenko; E. V. Alexandrova; A. S. Korjova (Zaporozhye State Medical University, 2014)
The aim of the work is thesynthesis and research of physical and chemical properties of earlier undescribed 1,8-disubstituted of theobromine, which are potential biologically active compounds. Materials and Methods of Research The melting point has been determined with the help of an open capillary method with TAP device (M). Elemental analysis has been performed with the help of the instrument ElementarVario L cube, NMR-spectra have been taken on a spectrometer Bruker SF-400 (operating frequency of 400 MHz, solvent DMSO-d6, internal standard - TMS). IR-spectra have been taken on Bruker Alpha Device Company in the 4000-400 cm-1area using console ATR (direct input material).These data correspond to thecalculated elemental analysis. Results and their discussion To achieve our goal, 8-bromotheobromine (1), obtained by the established method [9] of oxidizing theobrominebromination, has been selected as initial compound.8-Bromo-1-(4-fluorobenzyl)theobromine (2)has been synthesized with high entrance by bromotheobromine(1) and p-fluorobenzylchlorideboiling in dimethylformamide, in the presence of anequimolaramount of potassium caronate. Through the interaction of bromoxanthine (2) with the excess of hydrazine hydrate in the aqueous dioxanean 8-hydrazine-1(4-fluorobenzyl)theobromine (3)has been obtained, which under short-time heating up with aldehydes, isatin or 5-bromoisatin in aqueous dioxane, also presented with equimolaramount of НClconcentr.form respective ylidenhydrazine derivatives of 1-(4-fluorobenzyl)theobromine(4-13),which represent coloured crystalline compounds, insoluble in water, diethyl ether and lower alcohols, whilesoluble in hot dioxane, dimethylformamide and dimethylsulphoxide. To prove the structure of synthesized compounds, their NMR spectrahave beenrecorded and interpreted. In bromoxanthine spectrum (2) the presence of p-fluorobenzyl group in position 1 is clearly demonstrated by2 triplets of aromatic protons at 7.34 ppm and 7.09ppm with intensity in two proton units each. Methylene group protons, linked with a nitrogen atom in position 1 are recorded as intensive singlet at4.98 ppm (2Н).Protons of N-methyl groups in positions 3 and 7 of theobromine fragment are registered in a form of intensive singlets at 3.33 ppm (3Н) and 3.83 ppm (3Н) respectively. It is noteworthy that singlets of methylene and methyl group protons, bonded with nitrogen atoms of all the other synthesized compounds are registered with practically the same magnetic field intensity. Infrared spectrum of the initial bromoxanthine (2) shows no evidence of absorption band at3145 cm-1 (νNH), typical for8-bromotheobromine (1). Broad absorption bands at2980-3040 cm-1, conditioned by stretch vibrations of aromatic CH-bonds are observed in infrared spectra of compounds (2-13). In NMR spectrum of hydrazinoxanthine (3) signals made by protons from hydrazine residue are registered as singlets at 8.18 ppm (1Н, NH) and 4.33 ppm (2Н, NH2),that doesn't arise any doubts about its structure. Also, in NMR spectra of hydrazones 4-13, signals of NH2-group protons in hydrazine residue are not detected. Meanwhile, signals of NH-group protons in position 8 are shifted dramatically in a low field and are registered there as singlets within therange of 11.87-11.22 ppm (1Н).This is explained by the transition of a neighboring nitrogen atom to the sp2-hybrid state, which in its turn leads to itselectronegativity amplification. Methylidene protons of hydrazones 4-12 are registered as singlets in a fairly small range of 8.18-7.94 ppm. It should be noted that a singlet, determined by the resonance absorption of metyliden proton of 2-nitrobenzyliden derivative (4), is registered in the lowest field at 8.53 ppm, which can be explained by the formation of intramolecular hydrogen bond with an oxygen atom of a nitrogroup. All other signals of proton substituents in position 8, their location, shape and intensity are fully consistent with their structure. Conclusions Available laboratory methods have been elaborated to synthesize 8-benzylidenehydrazine-1-(4-fluorobenzyl)theobromines, which are prospective biologically active compounds. The structure of synthesized compounds has been provedby the data gathered from elemental analysis, IR- and PMR-spectroscopy.